Development Of Animation Videos To Improve Nutrition Awareness Of Elementary School Students In Rantau Rasau District - Prasetio, Dedi; Sukendro, Sukendro; Anjanika, Yonifia (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The development of animated videos as a learning media for nutrition for elementary school students in the Rantau Rasau District has proven to be effective and feasible to use. This is supported by several important findings. First, the validation results showed very good quality, with the assessment of media experts reaching a value of 46 and material experts reaching a value of 45 (both in the "Very Good" category with a range of 40-50). Second, trials in small groups showed a positive response with 80% of students giving a good rating and 20% of students giving a very good rating, with an overall average of 47.70. Furthermore, in the large group trial, consistent results were obtained with 66.7% of students giving a good rating and 33.3% giving a very good rating. Based on these results, it can be concluded that the animated video developed is not only valid in terms of content and media, but also practical in its implementation as a learning tool. This learning media has succeeded in achieving its goal of improving students' understanding of balanced nutrition and healthy eating patterns, as well as presenting nutritional information in an interesting and easy-to-understand way for elementary school students in Rantau Rasau District.